2021
DOI: 10.3906/tar-2102-76
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different drying methods and cold storage treatments on the postharvest quality and nutritional properties of P. ostreatus mushroom

Abstract: Cite as: Kibar B. Influence of different drying methods and cold storage treatments on the postharvest quality and nutritional properties of P. ostreatus mushroom. Turkish

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Because of these numerous benefits, there are now many ways to preserve the quality of mushrooms in general to increase their shelf-life. These approaches include applying both conventional and novel preservation techniques [15,16]. Balancing the benefits of extended shelf-life with maintaining the sensory and nutritional qualities of mushrooms is an ongoing challenge in the food industry.…”
Section: Introductionmentioning
confidence: 99%
“…Because of these numerous benefits, there are now many ways to preserve the quality of mushrooms in general to increase their shelf-life. These approaches include applying both conventional and novel preservation techniques [15,16]. Balancing the benefits of extended shelf-life with maintaining the sensory and nutritional qualities of mushrooms is an ongoing challenge in the food industry.…”
Section: Introductionmentioning
confidence: 99%
“…Results demonstrated that freeze-drying had little effect on the lipid composition of truffles so as to be a better way than heat-drying for truffle processing [16]. Kibar et al (2021) determined the effects of six different drying methods on the postharvest quality and nutritional properties (pH value, ash, protein, color, total phenolic content, total flavonoid content, antioxidant activity and element contents) of P. ostreatus mushroom, and showed that natural drying was the most effective treatment among drying methods, and it can be used successfully for long-term storage of this mushroom [17]. The researchers think that VFD is a good choice for drying Schizophyllum commune, due to the fact that this method could better maintain the primary color and natural form.…”
Section: Introductionmentioning
confidence: 99%
“…Oyster mushrooms (Pleurotus ostreatus) are the second most widely cultivated mushrooms in the world [1,2]. They have attracted increased attention due to their nutritional value and delicious taste [3].…”
Section: Introductionmentioning
confidence: 99%
“…Oyster mushrooms contain over 13 vitamins, such as Vitamin B groups and Vitamin C. It is worth mentioning that Vitamin B3 content in oyster mushroom is 5-10 times higher compared to any other vegetable, and calcium, phosphorus, and iron (with high bioavailability) content is approximately double the amount available in beef and pork meat [4]. In addition, mushrooms have a high percentage of high-quality proteins, containing all essential amino acids required by humans [2]. Therefore, mushrooms are considered a good substitute for high-protein foods that are also known as "meat free" (meat analogues), such as beef/chicken patties, nuggets, and sausages [5][6][7].…”
Section: Introductionmentioning
confidence: 99%